Effect of Backrest Inclination on Sitting Subjects Exposed to WBV. (2016) - Singh, Ishbir; Nigam, S.P.; Saran, V.H.
Abstract: This paper presents the result of experimental investigations which were conducted to assess the subjective response of seated human subjects under vertical harmonic vibrations. 12 human males were subjected to amplitudes of excitation (0.5, 1.0 and 1.5 m/s 2 rms) and frequencies of 5, 8, 12, 16 and 20 Hz. The effect of backrest inclination was studied for inclination angle of 0˚, 15˚ and 30˚. The responses from all the subjects in form of vibrations being felt by them at different body segments, their severity and significance and comfort level were recorded in subjective form. The results of the responses have been presented in the form of a pictorial representation. It has been observed that at low frequency excitations whole body vibrations (WBV) and upper portion of the body respond with mild to moderate vibrations. At high frequency excitations the lower portion of the body, which is close to the point of excitation, responds significantly. The response at excitation frequency closer to natural frequencies of different body segments is clearly evidenced in the form of vibratory effect on those segments. By and large with the increase in inclination of back rest, comfort level increases along with the shift of responding segments in certain cases.